2016
DOI: 10.1093/arclin/acw076
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data for the Montreal Cognitive Assessment in Middle-Aged and Elderly Quebec-French People

Abstract: Objective: Given that aging is associated with higher risk of cognitive decline and dementia, improving early detection of cognitive impairment has become a research and clinical priority. The Montreal Cognitive Assessment (MoCA) is a screening instrument used to assess different aspects of cognition. Despite its widespread use, norms adjusted to the sociodemographics of Quebec-French people are not yet available. Such norms are however important because performance on neuropsychological tests varies according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 30 publications
10
70
2
3
Order By: Relevance
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Consistent with previous findings, older age was associated with lower scores [11][12][13][14][15][16][17][18][31][32][33][34][35]. We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31].…”
Section: Discussionsupporting
confidence: 91%
“…We found a 1.0-point difference between the youngest (65-75) and oldest (75-85) groups; other studies have reported a difference of 0.6-2.4 points between similar age groups [13,[15][16][17]31]. Lower level of education was significantly associated with lower scores, correlating with results from other studies [11][12][13][14][15][16][17][18][31][32][33][34][35]. The difference in mean score was 1.4 points between the least and highest educated groups, in agreement with the original suggested method of adding an extra point for low education (≤12 years).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations